2022
DOI: 10.3389/fphar.2022.1055296
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic mechanism and clinical application of Chinese herbal medicine against diabetic kidney disease

Abstract: Diabetic kidney disease (DKD) is the major complications of type 1 and 2 diabetes, and is the predominant cause of chronic kidney disease and end-stage renal disease. The treatment of DKD normally consists of controlling blood glucose and improving kidney function. The blockade of renin-angiotensin-aldosterone system and the inhibition of sodium glucose cotransporter 2 (SGLT2) have become the first-line therapy of DKD, but such treatments have been difficult to effectively block continuous kidney function decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…TCM had the effect of modulating gut microbiota and improving glucose metabolisms in T2DM patients and pre-clinical experiments ( Zheng et al, 2021b ). Numerous studies reviewed the efficacy and mechanisms of Chinese herbal medicine on DKD, DR, and DPN, which have been reported to be critical for diabetes in the elderly ( Lu et al, 2019 ; Ai et al, 2020 ; Chen et al, 2022b ; Liu et al, 2022 ). Whlie TCM could give full play to the advantages of multiple targets and intervene in many important mechanisms of elderly diabetes.…”
Section: Tcm Treatments Of Elderly Diabetesmentioning
confidence: 99%
“…TCM had the effect of modulating gut microbiota and improving glucose metabolisms in T2DM patients and pre-clinical experiments ( Zheng et al, 2021b ). Numerous studies reviewed the efficacy and mechanisms of Chinese herbal medicine on DKD, DR, and DPN, which have been reported to be critical for diabetes in the elderly ( Lu et al, 2019 ; Ai et al, 2020 ; Chen et al, 2022b ; Liu et al, 2022 ). Whlie TCM could give full play to the advantages of multiple targets and intervene in many important mechanisms of elderly diabetes.…”
Section: Tcm Treatments Of Elderly Diabetesmentioning
confidence: 99%
“…Previous studies have demonstrated that Nrf2 plays a crucial role in responding to antioxidative stress and maintaining redox homeostasis. In the mechanism of DKD, in addition to Kelch-1ike ECH-associated protein l (Keap1)/Nrf2/antioxidant response element (ARE) signaling, Nrf2 can inhibit inflammation to relieve kidney damage by suppressing NF-κB, Sirtuin1 (SIRT1) and nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) 104 , 126 . Controversially, Nrf2 seems to have a dual effect in DKD.…”
Section: Ferroptosis-related Regulators Involved In Dkdmentioning
confidence: 99%
“…Extensive research findings indicate that the utilization of natural medications exhibits a positive impact on the management of DKD by restraining inflammation and oxidative stress. In addition, these drugs help modulate the gut microbiota and related metabolic processes [ 194 , 195 ].…”
Section: The Role Of Gut Microecological Interventions In Retarding T...mentioning
confidence: 99%